Corporate governance as antecedents and financial distress as a consequence of credit risk. Evidence from Iraqi banks - Abdullah Mohammed Sadaa; Yuvaraj Ganesan; Chu Ei Yet; Qutaiba Alkhazaleh; Alhamzah Alnoor; Ahmad Mohammad aldegis (Journal of Open Innovation: Technology, Market and Complexity, 2023)
This study examines the antecedents and consequences of credit risk (CR) in Iraqi banks' context from 2011 to 2020. POLS, FEM, and REM regression estimators were used to test the hypotheses after obtaining an appropriate model. The hypotheses test findings on CR antecedents reveal that the board's financial expertise, risk management committee, and foreign ownership have a negative impact on CR. Meanwhile, the results show an insignificant effect on CR of board independence, audit committee, institutional ownership, governmental ownership, and managerial ownership. Concentrating on the consequence of CR, the results stated that CR influenced financial distress (FD) positively. Finally, ownership concentration (OC) as moderating interacts with the association between CR and financial distress. The study enhances the knowledge and implications of the theory used for corporate governance dimensions. It provides feedback to regulators and policymakers on the effectiveness of corporate governance mechanisms regarding CR control. The study also offers the Iraqi regulators and policymakers evidence of the harmful impact of CR on financial distress, necessitating their protection of bank investors from such situations by improving established credit rules and laws. This study contributes to the existing body of knowledge by investigating the antecedents and consequences of credit risk in the banking sector. This study also took a further step by examining the moderating role of ownership concentration between CR and FD.